Analisis Strategi Pemasaran pada Perusahaan Jasa Travel Haji dan Umrah di Era New Normal - Yuzep Andiyawan; Afif Zaerofi; Andang Heryahya (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2023)
The growth of Umrah and Hajj travel business before the COVID-19 pandemic significantly incfreased. The COVID-19 pandemic caused Umrah and Hajj travel companies to experience losses. The new normal policy after the pandemic allows Umrah and Hajj travel companies to reopen their businesses. However, companies need to implement appropriate marketing strategies to maximize their profits. The goal of this research is to analyze the external and internal factors of X Tour & Travel, as well as the strategies used to increase the sales of umrah and hajj packages in the new normal era. The methods used were SWOT analysis, CPM, and QSPM. Research has shown that increased public enthusiasm for performing umrah and hajj is a primary opportunity for X Tour & Travel. The threat factors for X Tour & Travel include the lack of significant solutions from governments when policies change, high levels of business competition, and Saudi Arabia's unstable regulations in the new normal era. According to the QSPM matrix, the strategies that X Tour & Travel can implement include utilizing pilgrims' testimonies and endorsements on social media to provide insight to the public about umrah according to the sunnah, using various media and developing affordable umrah packages to cater to a wider community.